2-(4-Morpholinecarbothioylsulfanyl)acetic acid - Lo, K.M.; Ng, S.W. (International Union of Crystallography, 2010)
The asymmetric unit of the title compound, C(7)H(11)NO(3)S(2), contains two independent molecules with similar molecular structures. The morpholine ring adopts a chair conformation, and the C(2)N-C(=S)-S fragment is planar in the two independent molecules (r.m.s. deviations = 0.01 and 0.02 angstrom). The two molecules are disposed about a false center of inversion and are held together by a pair of O-H center dot center dot center dot O hydrogen bonds. The crystal studied was a racemic twin; the minor twin component refined to 17%.